Positive pole piece, electrochemical device comprising positive pole piece and electric device
By setting up a multi-layer active material layer in the lithium-ion battery electrode sheet to control the content and porosity of the lithium-enhancing material, the problem of battery performance degradation caused by the residue of lithium-enhancing material in the electrode sheet is solved, and more efficient lithium-ion release and battery performance improvement are achieved.
Patent Information
- Application Number
- CN202311156936.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
In existing lithium-ion batteries, lithium-ion material remains after release of Li, hindering the transmission of ions and electrons, resulting in reduced battery circulation performance and safety hazards.
By setting up a multi-layer active material layer in the electrode sheet, the content and porosity of the lithium supplement material in different layers are controlled, so that the content of the lithium supplement material at the level far away from the current collector is higher than that near the current collector, and the porosity difference is controlled within the range of 8%.
The lithium supplement material in the electrode sheet is achieved more consistent and fully lithium-release, improving the rate performance and circulation performance of the battery, and reducing safety risks.
Smart Images

Figure CN119581479A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and specifically provides a pole piece, an electrochemical device comprising the pole piece, and an electrical device. Background Art
[0002] With the continuous rapid development of large-scale energy storage, electric vehicles, consumer electronics and other fields, the demand for lithium-ion batteries is also growing. Many performances such as energy density, fast charging capability, safety and reliability are getting closer and closer to the limit. This requires seeking new breakthroughs in technology, innovating chemical systems, cell structures, and manufacturing processes, and then realizing the continuous improvement of the comprehensive capabilities of the new generation of lithium-ion batteries. In particular, in order to improve the energy density of current high-energy-density power batteries, the pole piece lithium replenishment method has begun to be introduced. After releasing Li, the pole piece lithium replenishment material will remain in the pole piece, becoming a shackle that hinders the transmission of ions and electrons; in addition, due to the problem of poor kinetics when the lithium replenishment material releases Li, it is easy for the lithium replenishment material at different distances from the current collector in the pole piece to release Li to different degrees, which will bring about the hidden danger of continuous gas production in the subsequent cycle process, affecting the battery cycle performance, and the safety test pass will also be greatly reduced. Summary of the invention
[0003] A first aspect of the present invention provides a pole piece, the pole piece comprising a current collector and a coating layer disposed on the current collector, the coating layer comprising N active material layers, N>1, and N is an integer, the first active material layer is disposed on the surface of the current collector, based on the total weight of the first active material layer, the content of the lithium supplement material in the first active material layer is C1, based on the total weight of the Nth active material layer, the content of the lithium supplement material in the Nth active material layer is CN, and wherein
[0004] C1<CN;
[0005] The porosity of the first active material layer is M1, the porosity of the Nth active material layer is MN, and wherein
[0006] |M1-MN|≤5%.
[0007] A second aspect of the present invention provides an electrochemical device, which includes the electrode sheet described in the first aspect.
[0008] A third aspect of the present invention provides an electrical device, which includes the electrochemical device described in the second aspect.
[0009] The beneficial effects of the present invention are:
[0010] The present invention controls the content of lithium-replenishing material in different active material layers in the pole piece so that the content of lithium-replenishing material in the active material layer far from the current collector is greater than the content of lithium-replenishing material in the active material layer close to the current collector, and controls the porosity difference between the Nth active material layer far from the current collector and the first active material layer close to the current collector within the range of 8%. On the one hand, the higher content of lithium-replenishing material in the active material layer close to the pole piece surface ensures that the lithium-replenishing material closer to the pole piece surface has a more excellent ion conduction path, thereby ensuring more consistent and more sufficient lithium release requirements of lithium-replenishing materials in different regions of the pole piece. On the other hand, the lithium-replenishing material close to the pole piece surface can improve the surface overpressure problem caused by the greater mechanical pressure on the pole piece surface during the pole piece forming process due to its higher mechanical compressive strength, and reduce the impact of the crushing of active material particles on the electrochemical performance. The porosity difference between the active material layer on the pole piece surface and the inner layer close to the current collector is controlled within a set range, thereby avoiding the problem of poor electrolyte wettability and ion migration uniformity caused by the uneven porosity in the thickness direction of the pole piece, thereby reducing the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to make the above-mentioned purpose, features and advantages of the present invention easier to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein, so the present invention is not limited to the specific embodiments disclosed below.
[0012] Figure 1 A cross-sectional view schematically shows the structure of a pole piece according to an embodiment of the present invention.
[0013] Figure 2 A cross-sectional view schematically shows the structure of a pole piece according to an embodiment of the present invention. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application. All other embodiments obtained by those skilled in the art based on the technical scheme provided by the present application and the embodiments given belong to the scope of protection of the present application.
[0015] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0016] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0017] In this application, "active material layer" refers to an active material distribution area with a certain thickness distributed in sequence in the thickness direction of the pole piece. The i-th active material layer can be formed by coating slurries of different raw materials on the pole piece current collector in a layered coating manner during the manufacturing process of the pole piece; or a layered area divided into a certain thickness interval along the thickness direction of the pole piece, and the thickness interval can be 10μm, 12μm, etc.
[0018] The "surface overpressure" in this application refers to the overpressure caused in the area close to the surface of the pole piece due to the uneven mechanical force in the thickness direction of the pole piece during the rolling process of the pole piece, and the surface porosity is relatively low compared with the inside of the pole piece. The "surface overpressure" in this application is expressed by P = 1-MN / Ma*100%, where Ma is the average porosity of the pole piece and MN is the porosity of the Nth active material layer of the pole piece. The pole piece is formed into a state of a structure with a porosity difference through the rolling step, and a pole piece with appropriate porosity requirements is obtained by adjusting the rolling pressure and rolling speed. The rolling pressure and rolling speed depend on the type and content of the active material and the lithium supplement material. Therefore, the rolling pressure and rolling speed can be controlled according to the type and content of the active material and the lithium supplement material to manufacture a pole piece with appropriate porosity.
[0019] It should be noted that the first active material layer is arranged on the surface of the current collector, the Nth active material layer is arranged as the active material layer farthest from the current collector, and the first to Nth active material layers are arranged in sequence along the thickness direction of the electrode sheet.
[0020] The present application provides a pole piece, which includes a current collector and a coating layer arranged on the current collector, wherein the coating layer includes N active material layers, N>1, and N is an integer, and the first active material layer is arranged on the surface of the current collector.
[0021] Based on the total weight of the first active material layer, the content of the lithium supplement material in the first active material layer is C1, based on the total weight of the Nth active material layer, the content of the lithium supplement material in the Nth active material layer is CN, and wherein
[0022] C1<CN;
[0023] The porosity of the first active material layer is M1, the porosity of the Nth active material layer is MN, and wherein
[0024] |M1-MN|≤5%.
[0025] Figure 1 and Figure 2 Schematic diagrams showing the content of lithium supplementing materials in different active material layers of the electrode when the N value is 2 and 3 respectively.
[0026] By making the content of lithium-replenishing material at the surface of the pole piece far away from the current collector higher than that at the surface close to the current collector in the thickness direction of the pole piece, on the one hand, the more consistent and sufficient lithium release requirements of the lithium-replenishing material in different areas of the pole piece can be met. On the other hand, the lithium-replenishing material at the surface can improve the overpressure problem that may exist in the pole piece preparation process due to its higher ability to resist mechanical pressure, avoid the crushing of active material particles and the uneven porosity inside the pole piece. At the same time, the porosity difference between the inner layer of the pole piece closest to the current collector and the outer layer farthest from the current collector is designed to be less than the set value, so that the pore distribution of the entire pole piece is uniform, which is conducive to the uniform infiltration of the electrolyte and the better uniformity of ion migration, which is beneficial to improving the electrochemical properties of the battery such as rate performance and cycle performance.
[0027] In some embodiments of the present application, there are an i-th active material layer, an i+1-th active material layer and a j-th active material layer in the first active material layer to the N-th active material layer, 1≤i≤N-1, 1≤j≤N-1, and i and j are integers, based on the total weight of the i-th active material layer, the content of the lithium supplement material in the i-th active material layer is Ci, based on the total weight of the i+1-th active material layer, the content of the lithium supplement material in the i+1-th active material layer is Ci+1, and wherein
[0028] Ci<Ci+1;
[0029] and / or,
[0030] The porosity of the i-th active material layer is Mi, the porosity of the j-th active material layer is Mj, and wherein
[0031] |Mi-Mj|≤(|ij| / (N-1))*5%.
[0032] The mechanical pressure on the pole piece during the rolling process gradually decreases from the pole piece surface to the inside, and the lithium supplement material is distributed in a gradient along the thickness direction inside the entire pole piece, corresponding to the change in the intensity of the mechanical pressure, that is, the surface of the pole piece with greater mechanical pressure has a relatively higher content of lithium supplement material, and so on, thereby preventing the pole piece surface from overpressure in the best way. At the same time, the gradient distribution of lithium supplement material in this way also meets the more consistent and sufficient lithium release requirements of lithium supplement material in different areas of the pole piece. The difference in porosity of any different active material layer of the pole piece is made less than the set value, thereby ensuring the uniformity of the pole piece structure and the uniformity of fast charge ion migration, and improving the electrochemical performance (such as high rate discharge performance, cycle stability) and safety performance of the battery.
[0033] In some embodiments of the present application, the lithium supplement material includes Li 5 FeO 4 , Li 6 CoO 4 , Li 2 NiO 2 , Li 6 MnO 4 After the lithium in the lithium supplement material is fully released, the solid phase material generated after decomposition still remains in the electrode. The solid phase material usually has low ionic conductivity and electronic conductivity. Preferably, the ionic conductivity of the lithium supplement material is less than 1*10 -6 S / cm, and the electronic conductivity is lower than 10S / cm, thereby improving the transportability of ions and electrons inside the electrode.
[0034] In some embodiments of the present application, based on the total weight of the Nth active material layer, the content of lithium supplement material in the Nth active material layer is CN, and 0.5 wt %≤CN<Ci≤10 wt %, preferably 2 wt %≤CN<Ci≤5 wt %.
[0035] In some embodiments of the present application, there is an i-th active material layer and a j-th active material layer in the first active material layer to the N-th active material layer, 1≤i≤N-1, 1≤j≤N-1, and i and j are integers, based on the total weight of the i-th active material layer, the content of the lithium supplement material in the i-th active material layer is Ci, based on the total weight of the j-th active material layer, the content of the lithium supplement material in the j-th active material layer is Cj, and wherein
[0036] |Ci-Cj|≤(|ij| / (N-1))*6%.
[0037] In some embodiments of the present application, the average porosity Ma of the pole piece satisfies: 20%≤Ma≤70%, preferably 20%≤Ma≤30%, and / or, MN satisfies: 20%≤MN≤70%, preferably 20%≤MN≤30%. By controlling the average porosity and surface porosity of the pole piece to be within the above range, the pore structure of the area close to the surface of the pole piece is improved, thereby making the kinetic process of lithium ions easier and improving the rate charge and discharge performance of the battery.
[0038] In some embodiments of the present application, the surface overvoltage P of the pole piece is 1-MN / Ma*100%, 0<P<12%. By controlling the surface overvoltage of the pole piece within the above range, the uniformity of porosity distribution inside the pole piece is ensured, thereby obtaining better electrolyte wettability and ion migration uniformity, thereby improving electrochemical performance (for example: rate charge and discharge performance).
[0039] In some embodiments of the present application, the average particle size D of the lithium supplement material is 10nm to 5μm, preferably 100nm to 1μm. If the particle size of the lithium supplement material is too large, the specific surface area will be too small, the electronic ion conduction network will be insufficient, and the lithium supplement agent will not be able to fully release lithium; if the particle size is too small, the difficulty of preparing the slurry will increase suddenly, causing the slurry to gel and agglomerate easily, affecting the manufacturability. At the same time, if the particle size is too small, the material itself will be too reactive, causing excessive consumption of electrolyte additives and solvent decomposition, resulting in increased gas production, affecting the electrochemical performance of the battery.
[0040] Electrochemical Devices
[0041] According to some embodiments of the present application, the electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The electrochemical device according to the present invention can be a secondary battery, such as a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0042] In some embodiments, the negative electrode plate is the negative electrode plate according to the present application, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material, a negative electrode composite lithium supplement material, a conductive agent and a binder.
[0043] In some embodiments, the negative electrode active material may be a commonly used negative electrode active material, including but not limited to: graphite, carbon material, silicon-based material, metal oxide, tin-based material. For example, silicon-based composite materials include but are not limited to silicon-carbon composite materials, silicon-metal oxide composite materials, silicon alloy composite materials. For example, metal oxides include but are not limited to iron oxide, lithium titanate, copper oxide, etc., which are regarded as all metal oxides that can be used for lithium extraction and storage.
[0044] In some embodiments, the conductive agent can be a commonly used conductive agent, including but not limited to: metal-based materials, carbon-based materials, conductive polymers and mixtures thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, nickel, copper, aluminum or silver. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, acetylene black, Ketjen black, carbon black, carbon fiber or any combination thereof. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0045] In some embodiments, the binder can be a commonly used binder, including but not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, ethylene oxide-containing polymers, carboxylated polyvinyl chloride, polyvinyl pyrrolidone, polyurethane, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0046] In some embodiments, the positive electrode sheet is a positive electrode sheet according to the present application. According to some embodiments of the present application, the positive electrode includes a current collector and a positive electrode active material layer located on the current collector, and the positive electrode active material layer includes a positive electrode active material, a positive electrode composite lithium supplement material, a conductive material and a binder. According to some embodiments of the present application, the positive electrode active material includes, but is not limited to: lithium cobalt oxide (LiCoO 2 ), lithium nickel cobalt manganese (NCM) ternary materials, lithium nickel cobalt aluminum (NCA) ternary materials, lithium iron phosphate (LiFePO 4 ), lithium iron manganese phosphate (LiMn x Fe 1-x PO 4 ) or lithium manganate (LiMn 2 O 4 ).
[0047] According to a preferred embodiment of the present application, the positive electrode active material is Li[Ni 1-x-y Co x M y ]O 2 (M=Mn, Al, etc., such as lithium nickel cobalt manganese oxide Li[Ni 1-x-y Co x Mn y]O 2 , 1-xy≥0.5, lithium nickel cobalt aluminum oxide Li[Ni 1-x-y Co x Al y ]O 2 , 1-xy≥0.5).
[0048] According to some embodiments of the present application, the positive electrode active material layer also includes a binder and optionally includes a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0049] According to some embodiments of the present application, the conductive material includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0050] The material and shape of the separator used in the embodiments of the present invention are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present invention.
[0051] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene and polyethylene terephthalate. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0052] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0053] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0054] The polymer layer contains polymers, and the polymer material is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxide, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0055] In some embodiments, the separator is a polyethylene (PE) separator coated with ceramic layers on both sides, wherein the PE layer thickness is in the range of 5 to 20 μm, and the coating thickness of each ceramic layer is in the range of 0 to 5 μm.
[0056] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0057] In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), or lithium difluorooxalatoborate.
[0058] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0059] In a preferred embodiment according to the present invention, the electrolyte is LiPF 6 / EC+DMC+EMC.
[0060] The electrochemical device according to the present invention can be used in electronic devices, including but not limited to laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0061] Test Method
[0062] Porosity test:
[0063] The testing method for the porosity of the i-th active material layer of the electrode is as follows: the electrode to be tested is corroded by acid to remove the current collector, and then the other electrode layers except the i-th active material layer to be tested are removed by plasma beam cutting technology (the interfaces of different active material layers can be distinguished by SEM of the electrode cross section), leaving only the intact i-th active material layer electrode, and then the above-mentioned i-th active material layer electrode sample with an intact area greater than 5cm2 is placed in a mercury porosimeter for testing, and the porosity of the i-th active material layer can be obtained.
[0064] The test method of the average porosity of the electrode is as follows: the electrode to be tested is placed in a mercury intrusion instrument for testing, and the porosity of the electrode obtained is the average porosity of the electrode.
[0065] Mean mass energy density:
[0066] Place the battery cell in a 45℃ environment and let it stand for 3h. When the battery cell reaches 45℃, discharge it to 3V at 0.7C and let it stand for 30min. Charge it to the cutoff current at 0.7C constant voltage and let it stand for 30min. Repeat the above steps 3 times, and measure the discharge energy each time, and calculate the average value Eeverage of the 3 discharge energies E. Measure the mass M of the battery cell with a scale, and calculate the average mass energy density PED, PED=Eeverage / M.
[0067] Cycle capacity retention rate:
[0068] Place the battery cell in a 45℃ environment and let it stand for 3h. When the battery cell reaches 45℃, charge it to 4.3V at 1.5C, then charge it to 4.48V at 0.7C, then charge it at 4.48V at a constant voltage to a cutoff current of 0.05C, and then discharge it to 3V at 0.5C. Record the initial capacity Q1. When the cycle reaches the required number of times, take the previous discharge capacity as the battery capacity Q2, and calculate the capacity retention rate, capacity retention rate (%) = Q2 / Q1×100%.
[0069] Specific capacity test of lithium stripping and insertion:
[0070] The battery cell is charged and discharged at a rate of 0.2C, and the capacity of lithium removal and lithium insertion of the battery cell is recorded. The above capacity is divided by the mass of the active material to calculate the lithium removal and lithium insertion specific capacity.
[0071] Example 1
[0072] (1) mixing negative electrode active material high energy density graphite, SiOx material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene-butadiene rubber, and conductive agent conductive carbon black according to a weight ratio of 82.8:14.6:0.6:0.6:0.6:0.8, adding deionized water, and obtaining negative electrode slurry under the action of a vacuum mixer; coating the negative electrode slurry on a 5 μm thick copper foil by an extrusion coater, and then drying and rolling to complete the preparation of the negative electrode sheet;
[0073] (2) Take nickel-cobalt-manganese ternary positive electrode active material (NCM811), PVDF, conductive carbon black, Li 2 NiO 2 The lithium supplement materials were mixed in a mass ratio of 93.5%:1.4%:1.1%:4.0%, NMP (N-methylpyrrolidone) was added, and positive electrode slurry 1 was obtained under the action of a vacuum mixer. Nickel-cobalt-manganese ternary positive electrode active material (NCM811), PVDF, conductive carbon black, Li 2 NiO 2 The lithium supplement material is mixed in a mass ratio of 91.5%:1.4%:1.1%:6.0%, and NMP (N-methylpyrrolidone) is added. The positive electrode slurry 2 is obtained under the action of a vacuum mixer. The positive electrode slurry 1 and the positive electrode slurry 2 are coated on the above-mentioned 10μm thick aluminum foil through an extrusion coater, wherein the positive electrode slurry 1 is coated on the side close to the current collector, and the positive electrode slurry 2 is coated on the side away from the current collector to complete the coating process. Then it is dried and rolled to complete the preparation of the positive electrode sheet;
[0074] (3) The positive electrode sheet and the negative electrode sheet are stacked together with the separator to prepare a bare cell, which is placed in a packaging bag, and then subjected to processes such as liquid injection, formation, capacity division and standing to obtain a lithium-ion battery.
[0075] Embodiment 2-8
[0076] With reference to Example 1, Examples 2 to 8 are carried out by changing the content of lithium supplement materials in different active material layers, particle size, and rolling conditions during the electrode rolling process (for example, rolling pressure, roll gap size, and controlling the rolling pressure of different embodiments to be within the range of 90±30 tons and the rolling speed to be within the range of 30±20 m / min), and the differences are shown in Table 1.
[0077] Example 9
[0078] (1) Mixing negative electrode active material high energy density graphite, SiOx (0<x<2) material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene-butadiene rubber, and conductive agent conductive carbon black according to a weight ratio of 82.8:14.6:0.6:0.6:0.6:0.8, adding deionized water, and obtaining negative electrode slurry under the action of a vacuum mixer; coating the negative electrode slurry on a 5 μm thick copper foil by an extrusion coater, and then drying and rolling to complete the preparation of the negative electrode sheet;
[0079] (2) Take nickel-cobalt-manganese ternary positive electrode active material (NCM811), PVDF, conductive carbon black, Li 2 NiO 2 The lithium supplement materials were mixed in a mass ratio of 94.5%:1.4%:1.1%:3.0%, NMP (N-methylpyrrolidone) was added, and positive electrode slurry 1 was obtained under the action of a vacuum mixer. Nickel-cobalt-manganese ternary positive electrode active material (NCM811), PVDF, conductive carbon black, Li 2 NiO 2 The lithium supplement materials were mixed in a mass ratio of 92.5%:1.4%:1.1%:5.0%, and NMP (N-methylpyrrolidone) was added to obtain positive electrode slurry 2 under the action of a vacuum mixer. Nickel-cobalt-manganese ternary positive electrode active material (NCM811), PVDF, conductive carbon black, Li 2 NiO 2 The lithium supplement material is mixed in a mass ratio of 90.5%:1.4%:1.1%:7.0%, and NMP (N-methylpyrrolidone) is added. The positive electrode slurry 3 is obtained under the action of a vacuum mixer. The positive electrode slurry 1, positive electrode slurry 2 and positive electrode slurry 3 are coated on the above-mentioned 10μm thick aluminum foil using an extrusion coater in a normal coating manner, wherein the positive electrode slurry 1 is coated on the side close to the current collector, the positive electrode slurry 3 is coated on the side away from the current collector, and the positive electrode slurry 2 is between the positive electrode slurry 1 and the positive electrode slurry 3, completing the coating process. Subsequently, drying, rolling, and slitting are performed to complete the preparation of the positive electrode sheet;
[0080] (3) The positive electrode sheet and the negative electrode sheet are stacked together with the separator to prepare a bare cell, which is placed in a packaging bag, and then subjected to processes such as liquid injection, formation, capacity division and standing to obtain a lithium-ion battery.
[0081] Embodiments 10 to 11
[0082] With reference to Example 9, Examples 10 to 11 are carried out by changing the content of lithium supplement materials in different active material layers, particle size, and rolling conditions during the electrode rolling process (for example, rolling pressure, roll gap size, and controlling the rolling pressure of different embodiments to be within the range of 90±30 tons and the rolling speed to be within the range of 30±20 m / min), and the differences are shown in Table 1.
[0083] Comparative Example 1
[0084] (1) mixing negative electrode active material high energy density graphite, SiOx (0<x<2) material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene-butadiene rubber, and conductive agent conductive carbon black in a weight ratio of 82.8:14.6:0.6:0.6:0.6:0.8%, adding deionized water, and obtaining negative electrode slurry under the action of a vacuum mixer; coating the negative electrode slurry on a 5 μm thick copper foil by an extrusion coater, and then drying and rolling to obtain a negative electrode sheet;
[0085] (2) Mix nickel-cobalt-manganese ternary positive electrode active material (NCM811), PVDF, and conductive carbon black in a mass ratio of 97.5%:1.4%:1.1%, add NMP (N-methylpyrrolidone), and obtain positive electrode slurry under the action of a vacuum mixer. Apply the positive electrode slurry on the above-mentioned 10 μm thick aluminum foil through an extrusion coater, and then dry and roll to obtain a positive electrode sheet;
[0086] (3) The positive electrode sheet and the negative electrode sheet are stacked together with the separator to prepare a bare cell, which is placed in a packaging bag, and then subjected to processes such as liquid injection, formation, capacity division and standing to obtain a lithium-ion battery.
[0087] Comparative Example 2
[0088] (1) mixing negative electrode active material high energy density graphite, SiOx (0<x<2) material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene-butadiene rubber, and conductive agent conductive carbon black in a weight ratio of 82.8:14.6:0.6:0.6:0.6:0.8%, adding deionized water, and obtaining negative electrode slurry under the action of a vacuum mixer; coating the negative electrode slurry on a 5 μm thick copper foil by an extrusion coater, and then drying and rolling to obtain a negative electrode sheet;
[0089] (2) Take nickel-cobalt-manganese ternary positive electrode active material (NCM811), PVDF, conductive carbon black, Li 2 NiO 2The lithium supplement material is mixed in a mass ratio of 92.5:1.4:1.1:5.0, NMP (N-methylpyrrolidone) is added, and a positive electrode slurry is obtained under the action of a vacuum mixer. The slurry is coated on the above-mentioned 10 μm thick aluminum foil through an extrusion coater, and then dried and rolled to obtain a positive electrode sheet;
[0090] (3) The positive electrode sheet and the negative electrode sheet are stacked together with the separator to prepare a bare cell, which is placed in a packaging bag, and then subjected to processes such as liquid injection, formation, capacity division and standing to obtain a lithium-ion battery.
[0091] The test results of each embodiment and comparative example are shown in the following table:
[0092]
[0093]
[0094] As can be seen from the above table, compared with Comparative Example 1 in which no lithium supplement material is added and Comparative Example 2 in which the lithium supplement material is not distributed according to a gradient, the battery comprising the pole piece of the present application has better rate performance and capacity cycle retention rate. Among them, the particle size of the lithium supplement material in Example 4 is relatively low, and at this time, the side reactions such as catalytic electrolyte decomposition are serious, resulting in a slightly lower cycle capacity retention rate of the battery than that of the batteries in other embodiments, but at the same time, the rate performance of the battery is relatively better.
[0095] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims, and these modifications and changes also fall within the scope of protection of the present invention.
Claims
1. A pole piece, characterized in that: The pole piece includes a current collector and a coating layer disposed on the current collector, wherein the coating layer includes N active material layers, N>1, and N is an integer, and the first active material layer is disposed on the surface of the current collector. Based on the total weight of the first active material layer, the content of the lithium supplement material in the first active material layer is C1, based on the total weight of the Nth active material layer, the content of the lithium supplement material in the Nth active material layer is CN, and wherein C1<CN; The porosity of the first active material layer is M1, the porosity of the Nth active material layer is MN, and wherein |M1-MN|≤5%.
2. The pole piece according to claim 1, characterized in that: The first active material layer to the Nth active material layer include an i-th active material layer, an i+1-th active material layer and a j-th active material layer, 1≤i≤N-1, 1≤j≤N-1, and i and j are integers. Based on the total weight of the i-th active material layer, the content of the lithium supplement material in the i-th active material layer is Ci, based on the total weight of the i+1-th active material layer, the content of the lithium supplement material in the i+1-th active material layer is Ci+1, and wherein Ci<Ci+1; and / or, The porosity of the i-th active material layer is Mi, the porosity of the j-th active material layer is Mj, and wherein |Mi-Mj|≤(|ij| / (N-1))*5%.
3. The pole piece according to claim 1, characterized in that: The lithium supplement material includes any one or more of Li5FeO4, Li6CoO4, Li2NiO2, and Li6MnO4.
4. The pole piece according to claim 2, characterized in that: Based on the total weight of the Nth active material layer, the content of the lithium supplementing material in the Nth active material layer is CN, and 0.5 wt %≤Ci<CN≤10 wt %, preferably 2 wt %≤Ci<CN≤8 wt %.
5. The pole piece according to claim 1, characterized in that: There are an i-th active material layer and a j-th active material layer in the first active material layer to the N-th active material layer, 1≤i≤N-1, 1≤j≤N-1, and i and j are integers, based on the total weight of the i-th layer, the content of the lithium supplement material in the i-th active material layer is Ci, based on the total weight of the j-th active material layer, the content of the lithium supplement material in the j-th active material layer is Cj, and wherein |Ci-Cj|≤(|ij| / (N-1))*6% 6. The pole piece according to claim 1, characterized in that: The average porosity Ma of the pole piece satisfies: 20%≤Ma≤70%, preferably 20%≤Ma≤30%, and / or, MN satisfies: 20%≤MN≤70%, preferably 20%≤MN≤30%.
7. The pole piece according to claim 6, characterized in that: The surface overvoltage P of the pole piece is 1-MN / Ma*100%, wherein 0<P<12%.
8. The pole piece according to claim 1, characterized in that: The average particle size D of the lithium supplement material is 10 nm to 5 μm, preferably 100 nm to 1 μm.
9. An electrochemical device, characterized in that: The electrochemical device comprises a pole piece according to any one of claims 1 to 8.
10. An electrical device, characterized in that: The electrochemical device comprises the electrochemical device according to claim 9.